2020
DOI: 10.1111/1346-8138.15521
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world efficacy and safety data of nivolumab and ipilimumab combination therapy in Japanese patients with advanced melanoma

Abstract: The efficacy and safety of nivolumab + ipilimumab combination therapy were retrospectively examined in Japanese patients with unresectable advanced melanoma in clinical practice. Fifty‐seven patients with advanced melanoma received the nivolumab + ipilimumab combination therapy. The primary site was cutaneous, mucosal, uveal and unknown in 35, 16, two and four patients, respectively. The overall response rate was 26.3%, with complete response observed in two (3.5%) patients, partial response in 13 (22.8%), sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
32
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 24 publications
4
32
1
Order By: Relevance
“…Four studies have tested the efficacy of PD1 plus radiotherapy, including a study recently reported by our group, 22 , 23 , 24 , 25 two studies have tested PD1 plus a vascular endothelial growth factor receptor (VEGFR) inhibitor, 26 , 27 and four studies explored the efficacy of PD1 + CTLA4. 6 , 16 , 17 , 28 , 29 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Four studies have tested the efficacy of PD1 plus radiotherapy, including a study recently reported by our group, 22 , 23 , 24 , 25 two studies have tested PD1 plus a vascular endothelial growth factor receptor (VEGFR) inhibitor, 26 , 27 and four studies explored the efficacy of PD1 + CTLA4. 6 , 16 , 17 , 28 , 29 …”
Section: Discussionmentioning
confidence: 99%
“… 28 , 29 A single-institutional retrospective study that included 16 Japanese MCM patients showed an ORR of 12.5% (25% among the 8 patients who received PD1 + CTLA4 as a first-line therapy) and a median PFS of 2.6 months; the median OS was not reached. 6 In a Caucasian population, a pooled analysis of the CheckMate-067 and CheckMate-069 cohorts (35 MCM patients) showed that nivolumab plus ipilimumab displayed more favorable activity than nivolumab monotherapy, with an ORR of 37.1% and a median PFS of 5.9 months, although statistical analysis was not carried out. 16 Shoushtari et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RR of combined nivolumab and ipilimumab therapy for MCM as the second-line treatment was 0%, whereas it was 20% for cutaneous melanoma. 7 Moreover, the RR of ipilimumab monotherapy after progression on anti-programmed cell death protein 1 antibody monotherapy was reported as only 3Á6%. 8 Our study was limited by its retrospective design and small sample size.…”
mentioning
confidence: 99%
“…6 Similar maximum doses (400 mg m -2 ) have been proposed in nodal T-cell lymphomas. 7 We report our experience with PEG-DOXO (Caelyx â ) as a maintenance strategy in advanced-stage MF, describing 18 patients who continued to receive doxorubicin following an initial response. Patient characteristics are shown in Table 1.…”
mentioning
confidence: 99%